2014
DOI: 10.1371/journal.pone.0088540
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy and Subsequent Treatment with Estrogen Receptor Agonists Tune the Innate Immune System of the Hippocampus in Middle-Aged Female Rats

Abstract: The innate immune system including microglia has a major contribution to maintenance of the physiological functions of the hippocampus by permanent monitoring of the neural milieu and elimination of tissue-damaging threats. The hippocampus is vulnerable to age-related changes ranging from gene expression to network connectivity. The risk of hippocampal deterioration increases with the decline of gonadal hormone supply. To explore the impact of hormone milieu on the function of the innate immune system in middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 77 publications
4
29
1
4
Order By: Relevance
“…Our previously published studies demonstrated elevations in inflammasome proteins in the hippocampus of aged rats [41,42]. Consistent with our findings, others have demonstrated increased pro-inflammatory cytokine levels in middle-aged female rats [43]. It is now well documented that the depletion of estrogens at menopause /reproductive senescence elevates pro-inflammatory cytokines, which may increase the chances of inflammatory diseases in the body, including the brain.…”
Section: Discussionsupporting
confidence: 92%
“…Our previously published studies demonstrated elevations in inflammasome proteins in the hippocampus of aged rats [41,42]. Consistent with our findings, others have demonstrated increased pro-inflammatory cytokine levels in middle-aged female rats [43]. It is now well documented that the depletion of estrogens at menopause /reproductive senescence elevates pro-inflammatory cytokines, which may increase the chances of inflammatory diseases in the body, including the brain.…”
Section: Discussionsupporting
confidence: 92%
“…RNA quality was assessed with capillary electrophoresis using Pico RNA Chips on a 2100 Bioanalyzer (Agilent, Santa Clara, Calif., USA) [25]. The RNA samples processed further for qPCR studies exhibited RNA integrity numbers between 6.2 and 7.5.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription of 10 ng total RNA was carried out using routine procedures and the SuperScript VILO III cDNA reverse transcription kit (Life Technologies, Carlsbad, Calif., USA) [25]. The quantity of the targeted cDNAs was increased with the TaqMan PreAmp Master Mix Kit (Thermo Fisher Scientific, Pittsburgh, Pa., USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increasing the expression of Sema3A contributes to the regeneration of bone defects and titanium implant fixations in ovariectomized (OVX) animals [16, 17] as well as the improvement of osseointegeration in type 2 DM rats [18]. However, whether Sema3A and the associated proteins of β-catenin and IGF-1 are involved in alterations of bone microstructure and strength of diabetic rats remains unclear.…”
Section: Introductionmentioning
confidence: 99%